A-PRESERVE: Airlangga Perineal Repair Workshop for Health Service in Surabaya - Kurniawati, Eighty Mardiyan; Wahyuningtyas, Riska; Hardianto, Gatut; Hadi, Tri Hastono Setyo; Putra, M. Dimas Abdi; Rahmawati, Nur Anisah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Perineal rupture is a common complication during childbirth that requires appropriate management to prevent further morbidity. The knowledge and skills of midwives and general practitioners in performing perineal tear suturing at primary health care centers are crucial to ensure optimal care and minimize the risk of complications while promoting faster recovery of patients. Objective: This community service activity aims to improve the knowledge and skills of midwives and general practitioners in suturing perineal tears through workshops and training at primary health facilities. Method: The workshop was attended by 40 participants, consisting of midwives and general practitioners, for 150 minutes. The activity included training on perineal anatomy, suturing techniques, post-repair management, and practical suturing simulation using a cow tongue model. Participants completed questionnaires covering demographic data, and pre- and post-tests consisting of 10 questions about perineal tear repair. Result: Most participants were women in the productive age range, with a majority holding bachelor's degrees. Only a few had prior experience attending suturing workshops. Pre-test results showed lower knowledge compared to post-test results. The mean rank for pretest was 26.18 while posttest was 54.83, with a p-value of 0.000, indicating a statistically significant improvement in participants’ knowledge after the intervention. Conclusion: The workshop were effective in enhancing the knowledge of midwives and general practitioners in managing perineal tears. The findings highlight the importance of routine technical training to elevate the quality of childbirth care in public health centers.